Extended lagrange multiplier selection for hybrid video coding using interframe correlation - Li, Xiang; Örtel, Anne; Hutter, A.; Kaup, André (26th Picture Coding Symposium, PCS 2007, 2007)
The Lagrange multiplier based rate-distortion optimization has been proved an effective technique in hybrid video codec design. To improve the coding efficiency, an efficient La-grange multiplier selection method is presented in this paper. As an extension to our previous work, the Laplace distribution based rate model is further refined by taking correlations among successive frames into account, so that the proposed method shows a superior performance over previous algorithms. Compared with the most recent reference software of H. 264/AVC, a gain of 0.26dB on average, 1.3dB at maximum, was achieve
Keywords: Hybrid video coding; Lagrange multiplier selection; Rate-distortion optimization